1993
DOI: 10.1073/pnas.90.8.3710
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophin protects the sarcolemma from stresses developed during muscle contraction.

Abstract: The protein dystrophin, normally found on the cytoplasmic surface of skeletal muscle cell membranes, is absent in patients with Duchenne muscular dystrophy as well as mdx (X-linked muscular dystrophy) mice. Although its primary structure has been determined, the precise functional role of dystrophin remains the subject of speculation. In the present study, we demonstrate that dystrophin-deficient muscle fibers of the mdx mouse exhibit an increased susceptibility to contraction-induced sarcolemmal rupture. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
1,117
2
4

Year Published

1993
1993
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,301 publications
(1,160 citation statements)
references
References 33 publications
37
1,117
2
4
Order By: Relevance
“…AdV-Dys efficacy in protecting adult mdx muscle from contraction-induced mechanical stress It was previously demonstrated that dystrophin-deficient myofibers exhibit an abnormally increased susceptibility to contraction-induced injury that is reflected by an accelerated loss of isometric force-generating capacity following the imposition of high-stress eccentric contractions. 5 Therefore, we also determined the effects of AdV-Dys administration on the vulnerability of mdx soleus muscles to this form of damage. As depicted in Figure 7, both AdV-Dys and control mdx muscles exhibited reductions in force-generating capacity over the course of the eccentric contraction protocol.…”
Section: Optimization Of Adv-dys Inoculum Dosagementioning
confidence: 99%
See 3 more Smart Citations
“…AdV-Dys efficacy in protecting adult mdx muscle from contraction-induced mechanical stress It was previously demonstrated that dystrophin-deficient myofibers exhibit an abnormally increased susceptibility to contraction-induced injury that is reflected by an accelerated loss of isometric force-generating capacity following the imposition of high-stress eccentric contractions. 5 Therefore, we also determined the effects of AdV-Dys administration on the vulnerability of mdx soleus muscles to this form of damage. As depicted in Figure 7, both AdV-Dys and control mdx muscles exhibited reductions in force-generating capacity over the course of the eccentric contraction protocol.…”
Section: Optimization Of Adv-dys Inoculum Dosagementioning
confidence: 99%
“…After completing contractility measurements in the soleus muscles, mice were killed by anesthetic overdose and the diaphragm was removed en bloc with its intact rib cage as previously described. 5,29 Contractility measurements were then made in random order on muscle strips obtained from each side of the diaphragm.…”
Section: Measurement Of Isometric Contractile Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, GRMD dogs suffer a severe and rapidly progressing muscle disease with premature lethality more closely resembling DMD in humans while mdx mice exhibit a milder phenotype with no dramatic reduction in lifespan [3]. Thus, it appears that compensatory cytoskeletal remodeling is not as effective in dystrophin-deficient dogs compared to mice, which may be due to the greater mechanical stresses imposed on the sarcolemma of larger animals with correspondingly larger myofibers [30,41]. More interestingly, we demonstrated that daily treatment with prednisone correlated with a significant elevation in γ cyto -actin levels in GRMD skeletal muscle as compared to muscle from non-treated GRMD dogs.…”
Section: Resultsmentioning
confidence: 99%